Peran Kepuasan Kerja dan Komitmen Organisasional Terhadap Kebahagiaan Di Tempat Kerja - Felicia, Monica; Pramudita, Dismas Persada Dewangga; Palupi, Rosa De Lima Dyah Retno; Bhimasta, Raden Agoeng (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2024)
This study investigates the influence of job satisfaction and organizational commitment on employee happiness at work. Adopting a quantitative research approach, data were collected through a structured survey involving 53 employees of PT. Global Intermedia Nusantara (Provider of consulting services, analysis, design and implementation of information systems in the company). The Partial Least Square (PLS) analysis model was applied to explore the interrelationships among the variables. The findings indicate that job satisfaction plays a pivotal role in enhancing happiness at work, with employees reporting greater contentment when their job expectations and needs are met. Additionally, organizational commitment emerges as a critical factor, demonstrating a strong positive impact on workplace happiness. This suggests that employees who feel emotionally attached to their organization and aligned with its goals tend to experience higher levels of happiness. The results of this study indicate a positive and significant effect of job satisfaction on happiness at work. Organizational commitment is also proven to have a positive and significant effect on employee happiness at work. These results underline the need for organizations to prioritize strategies that cultivate job satisfaction and reinforce organizational commitment.